2019
DOI: 10.3389/fpsyg.2019.00674
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Complexity Preferences for Music

Abstract: Recently, we demonstrated complexity as a major factor for explaining individual differences in visual preferences for abstract digital art. We have shown that participants could best be separated into two groups based on their liking ratings for abstract digital art comprising geometric patterns: one group with a preference for complex visual patterns and another group with a preference for simple visual patterns. In the present study, building up on these results, we extended our investigations for complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…These findings are in line with those ofGüçlütürk et al (2016),Güçlütürk and van Lier (2019), andMarin and Leder (2018), highlighting the importance of understanding individual differences that coexist with general trends. The estimated individual aesthetic sensitivities for musical balance (-0.482, -0.126), symmetry (0.160, 0.233), and rhythmic contour (-0.365, -0.059) varied within one pole, pointing to a consistent tendency across participants.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…These findings are in line with those ofGüçlütürk et al (2016),Güçlütürk and van Lier (2019), andMarin and Leder (2018), highlighting the importance of understanding individual differences that coexist with general trends. The estimated individual aesthetic sensitivities for musical balance (-0.482, -0.126), symmetry (0.160, 0.233), and rhythmic contour (-0.365, -0.059) varied within one pole, pointing to a consistent tendency across participants.…”
supporting
confidence: 85%
“…Specifically, we wished to characterize musical aesthetic sensitivity to four attributes that figure prominently in the literature on visual aesthetics: balance, contour, symmetry, and complexity. There is some evidence for common effects of complexity on the appreciation of visual and musical materials (e.g., Marin, Lampatz, Wandl, & Leder, 2016;Marin & Leder, 2013) and there is also some evidence for individual differences in aesthetic sensitivity to complexity (Güçlütürk, Jacobs, and van Lier, 2016;Güçlütürk & van Lier, 2019;Marin & Leder, 2018).…”
Section: Musical Aesthetic Sensitivitymentioning
confidence: 99%
“…Preference for musical complexity has been thought to follow an inverted U-curve; very simple or extremely complex pieces are less liked than pieces of moderate complexity. Recent research indicates that it is more revealing to consider two groups of subjects: those who prefer simplicity and those who prefer complex stimuli (Güçlütürk and van Lier, 2019). These two groups were found to be separated by age, gender and the personality trait of being susceptible to systemising and analysing.…”
Section: Discussionmentioning
confidence: 99%
“…Things happen to be even more intricate than just suggested, for if, on the one hand, plenty of studies have shown a preference of humans for medium entropy, on the other hand, an increasing number of studies demonstrate that the preferred level of entropy is highly variable across individuals (e.g., Güçlütürk et al 2016;Güçlütürk & van Lier 2019). This line of research suggests that the relationship between liking and entropy may be largely shaped by cultural factors, and as a consequence, that any normative claim for example, "humans seek to minimize entropy"is pointless.…”
Section: Introductionmentioning
confidence: 99%